2006
DOI: 10.1002/anie.200503068
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Oxygen Defects in the Catalytic Performance of Zinc Oxide

Abstract: ”Systematic errors”, namely, oxygen vacancy sites in ZnO, are the active centers for the hydrogenation of CO to give methanol. Nanocrystalline ZnO with a high density of oxygen vacancies was prepared from special organometallic precursors, and its catalytic properties for methanol synthesis were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
192
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 246 publications
(203 citation statements)
references
References 45 publications
8
192
0
3
Order By: Relevance
“…Since the surface layer is only ZnO, it has been revealed that V O s can behave as important adsorption and active sites for catalysis, which strongly inuence the reactivity of metal oxides. 77 Notably, V O ++ forms aer capturing a hole from the VB.…”
Section: Role Of Holesmentioning
confidence: 99%
“…Since the surface layer is only ZnO, it has been revealed that V O s can behave as important adsorption and active sites for catalysis, which strongly inuence the reactivity of metal oxides. 77 Notably, V O ++ forms aer capturing a hole from the VB.…”
Section: Role Of Holesmentioning
confidence: 99%
“…Using pyrolysis and gasification both can be successfully transformed to syngas 1, 2 which, in turn, is used in methanol formation. [3][4][5][6] Zeolite ZSM-5 is a well-known catalyst of MTH and MTG transformations. 7 Although this catalyst was used in the MTG process from early 1970s, its deactivation by coke formation dampened its applications.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the degree of complexity reached by the real catalytic systems (either at the industrial scale or the laboratory scale), it is often mandatory to go beyond the ideal surface approach at low coverage. This is particularly true when defects cannot be described by specific cleavage orientations of the bulk materials, such as for low-coordinated sites of nano-aggregates, extra-framework species or vacancies, [52][53][54][55][56][57][58][59][60][61][62] and when they dominate the surface reactivity of solids. It is also mandatory to address the complexity of the system for supported catalysts when support effects are suspected to influence directly or indirectly the reactivity.…”
Section: Introductionmentioning
confidence: 99%